Critical pedagogies, life and good living. (By Sigfredo Chiroque Chunga) - Navarro-Navarro, Bertha Consuelo (2024)
The book is divided into two parts. In the first, "Life, learning and education," Chiroque examines the relationship between life and nature, highlighting that learning and education only make sense when they are oriented toward "good living" or allin kawsay. The second part, "Critical pedagogies for good living," calls for the construction of a dynamic and democratizing educational model that prioritizes good living without colonialism. Here, Chiroque explores critical pedagogy as a tool to challenge socioeconomic systems contrary to life and social well-being, and promotes a transformative and disruptive education that values ​​ancestral knowledge and incorporates decoloniality and interculturality into the curriculum. Research in teacher training is central to an education that contributes to a "desirable and possible political project" that promotes both science and utopia.